Multi-cyber framework for availability enhancement of cyber physical systems - Parvin, Sazia; Hussain, Farookh Khadeer; Hussain, Omar; Thein, T.; Park, J. (Springer Vienna, 2012)
With the rapid growth of wireless communication, the deployment of cyber-physical system (CPS) is increasing day by day. As a cyber-physical system involves a tight coupling between the physical and computational components, it is critical to ensure that the system, apart from being secure, is available for both the cyber and physical processes. Traditional methods have generally been employed to defend an infrastructure system against physical threats. However, this does not guarantee that the availability of the system will always be high. In this paper, we propose a multi-cyber (computational unit) framework to improve the availability of CPS based on Markov model. We evaluate the effectiveness of our proposed framework in terms of availability, downtime, downtime cost and reliability of the CPS framework.